From 2-D Nanocrystalline Films to 1-D Nanomaterials: An Overview. (19th February 2018) - Pan, Chunxu; Wu, Jun; Song, Gongsheng; Luo, Chengzhi; Li, Delong; Liu, Yueli; Fu, Qiang
ABSTRACT: In the past few years, our group worked on the area of transformation from the two-dimensional (2-D) nanocrystalline films to one-dimensional (1-D) nanomaterials by using thermal oxidation. In this paper, we overview the research work on the controllable growth processes, transformation phenomena, growth mechanisms and applications. In general, the preparation process includes the following steps: 1) prepare a pure metal nanocrystalline film via a pulse electro – deposition; 2) grow variant 1-D nanomaterials, such as carbon nanotubes (CNTs), carbon nanofibers (CNFs), and 1-D metal oxide nanoneedles involving ZnO, CuO and Fe3 O4, etc. by using this film as catalyst. This process exhibits the following features: 1) the 1-D nanomaterials grow according to "base growth" model and no residual catalyst exists at the tip of the products; 2) the diameter of the 1-D nanomaterials can be controlled by controlling grain sizes of the 2-D films through adjusting pulse electro-deposition parameters; 3) it is more easily to get the 1-D nanomaterials with large area, uniform, vertical alignment and good shape on the substrates. We propose a "solid state based-up diffusion growth mechanism" for growth of the 1-D metal oxide nanoneedles, and "base growth model" for the 1-D carbon nanomaterials. The physical properties, such as Field emission and magnetics, of the 1-D metal oxide nanoneedles were studied, which showed desired values. In addition, we couple the ZnO nanoneedles with NiO, TiO2, graphene, Au nanoparticles, etc. for enhancing photocatalytic properties in the areas of environmental purification.